Al-Jadal al-Kalāmī Bayn Nahḍah al-Ulamā’ wa al-Wahhābiyah fī ‘Facebook’: Ṣafhah ‘Abd al-Wahhāb Ahmad Namūdzajan: The Theological Debate between Nahdatul Ulama and Wahhabi on Facebook: An Analysis of Abdul Wahab Ahmad - Ryandi Ryandi (Tasfiyah: Jurnal Pemikiran Islam, 2023)
The article discusses the struggle for the “Aswaja theological authority” between the Nahdatul Ulama (NU) and Wahhabi groups on Facebook. This article records how the forms, issues and shifts of the discourse. The study was carried out by observing young NU elite accounts who actively criticized Wahhabi theology on facebook. Data analysis uses discourse analysis. The study found that the struggle for the "Aswaja theological authority" was carried out by the Wahhabi group's post which the NU group responded to. The struggle for the " Aswaja theological authority" was carried out by presenting both classical and contemporary Ulama books from each group. The most discussed theological issues are related to the nature of God, Prophethood, and ‘is Ash'aria Ahlusunnah’? Finally, the struggle for "Aswaja's theological authority" underwent a shift, shifting religious authority, namely complicated theological polemics, and turats on social media have become a common commodity, which anyone is welcome to comment on.